MODERN ASPECTS OF THE COMBINED PATHOLOGY: BRONCHIAL ASTHMA AND DISEASES OF THE UPPER GASTROINTESTINAL TRACT SEGMENTS AMONG CHILDREN - S.K. Arshba (Union of pediatricians of Russia, 2008)
The article is devoted to the combined pathology in childhood, namely a combination of bronchial asthma and gastroesophageal reflux disease. The authors highlighted the key theories of the disease etiopathogenesis under alternating environmental conditions. They also highlighted the results of their own studies.Key words: bronchial asthma, gastroesophageal reflux disease, children.